2011
DOI: 10.1073/pnas.1015063108
|View full text |Cite|
|
Sign up to set email alerts
|

Nucleotide oligomerization domain-containing proteins instruct T cell helper type 2 immunity through stromal activation

Abstract: Although a number of studies have examined the development of T-helper cell type 2 (Th2) immunity in different settings, the mechanisms underlying the initiation of this arm of adaptive immunity are not well understood. We exploited the fact that immunization with antigen plus either nucleotide-binding oligomerization domain-containing proteins 1 (Nod1) or 2 (Nod2) agonists drives Th2 induction to understand how these pattern-recognition receptors mediate the development of systemic Th2 immune responses. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 49 publications
8
65
1
1
Order By: Relevance
“…19 In this study, dendritic cells were found to be the major hematopoietic cell population required. However, it is still possible that MCs may contribute to optimal Th2 orchestration via NOD signaling in other settings.…”
Section: How Do Mast Cells Sense Gastrointestinal Helminthmentioning
confidence: 99%
“…19 In this study, dendritic cells were found to be the major hematopoietic cell population required. However, it is still possible that MCs may contribute to optimal Th2 orchestration via NOD signaling in other settings.…”
Section: How Do Mast Cells Sense Gastrointestinal Helminthmentioning
confidence: 99%
“…Nod1 and Nod2 stimulation ultimately leads to NF-kB activation and the subsequent production of proinflammatory cytokines. Nod1/2 activation polarizes humoral responses toward Th2 yet enhances TLR-mediated Th1 immunity (38)(39)(40). These two receptors play critical functions at mucosal surfaces.…”
mentioning
confidence: 99%
“…Magalhaes et al [73] showed that MDP activation of the NOD2-mediated pathway in DCs is insufficient to initiate Th2 immunity in absence of stromal-derived mediators, such as thymic stromal lymphopoientin (TSLP). TSLP is thought to promote Th2 immunity by an up-regulation of the expression of OX40 ligand (OX40L), which is a transmembrane protein expressed by APCs to recognize OX40, a receptor expressed by T cells [74,75].…”
Section: The Mdp-nod2 Pathway and T Helper Cell Regulationmentioning
confidence: 99%
“…Moreover, OX40 deficient mice had diminished capabilities in generating NOD2-drived Th2 immunity [73].…”
Section: The Mdp-nod2 Pathway and T Helper Cell Regulationmentioning
confidence: 99%